Pengembangan Strategi Pembelajaran Kreatif dan Inovatif Pendidikan Agama Islam (PAI) di Era Digital - Fathimah Raniyah; Nur Hasnah; Gusmaneli Gusmaneli (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
In this modern era, Islamic religious education is an integral part of the education systemsignificant transformation along with technological developments in the digital era. Development Learning methods are important to ensure that students canintegrating Islamic religious values ​​with the context of their digital lives. This studyaims to explore and develop innovative deep learning methodsIslamic religious education in the digital era. The results of this research indicate that the approachtechnology-based, such as the use of mobile applications, dare platforms, and multimediainteractive, can increase student engagement and learning effectiveness.This research also highlights the importance of integrating Islamic ethical and moral values ​​in designdigital learning. By combining Islamic aspects with technology, methodsThis learning not only provides a deep understanding of the Islamic religion,but also prepare students to face ethical challenges in the digital era. ResultsIt is hoped that this research can make a positive contribution to curriculum developmentand Islamic religious education learning practices. Thus, Islamic religious educationin the digital era it can be an effective vehicle for forming a generation that is not onlyTechnologically competent, but also has a solid moral foundation in line withIslamic religious teachings.